APOB: old gene, new perspective for Familial Hypercholesterolaemia - Alves, A.C. (2013)
Familial hypercholesterolemia (FH) is one of the most common diseases of lipid metabolism, has an autosomal dominant inheritance and was the first genetic disorder of lipid metabolism to be characterized molecularly. FH usually results from inherited defects in the low density lipoprotein receptor (LDLR) gene and is characterised by increased circulating low density lipoprotein (LDL) cholesterol that leads to lipid accumulation in arteries and tendons (xanthomas), causing premature arteriosclerosis and coronary heart disease. Mutations in other genes as the apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 gene (PCSK9) are rare causes of FH. Until now only a few mutations in exon 26 and 29 have been reported to cause FH, being the APOB3527 the most common. The main aim of this project was to identify and characterize the genetic cause of severe hypercholesterolaemia in individuals with clinical diagnosis of FH, without mutations in LDLR and PCSK9 or in fragments of exon 26 and 29 of APOB routinely screened.